PENERAPAN METODE FUZZY SUGENO UNTUK MENENTUKAN HARGA JUAL SEPEDA MOTOR BEKAS - AGUSTIN, AMI HILDA; GANDHIADI, G. K.; OKA, TJOKORDA BAGUS (E-Jurnal Matematika; Vol 5 No 4 (2016), 2016)
Fuzzy logic is a way to map an input space into an output space. The basic of fuzzy logic is fuzzy set theory. In the fuzzy set theory, the role of membership degree is important to determine the presence of elements in a set. Membership degree is the fundamental feature of reasoning in fuzzy logic. There are several methods that are often used in solving fuzzy inference system, one of them is fuzzy Sugeno method. The aim of this research is applications of fuzzy methods is to forecast to determine the selling price of used motorcycles. In determining the selling price of used motorcycles, there are several things that need to be considered, namely : the production year of the motorcycles, the physical condition of the motorcycles, the origin of the license plates, and the purchase price of the motorcycles. The calculation can be done by using Matlab program. The result obtained were then tested using the Mean Absolute Percentage Error (MAPE) by calculating difference between the selling price of dealer minus the selling price of fuzzy Sugeno then divided by the selling price of dealer. From the test result, MAPE value obtained was 5,64% . This indicates that error rate below 10%, so we can say the result of these calculation is considerably accurate.
Keywords: Fuzzy Sugeno Method; Matlab, MAPE; Used Motorcycle